2009
DOI: 10.1007/s12291-009-0034-x
|View full text |Cite
|
Sign up to set email alerts
|

Stimation of reference interval of lipid profile in Assamese population

Abstract: 170 (93-263); 110 (40-256); 40 (23-73); 103 (40-173) and 22 (8-51)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 3 publications
3
16
5
Order By: Relevance
“…Recent studies from different geographical locations of India have established reference intervals for certain biochemical parameters and also identified significant changes in liver markers and lipid levels in healthy Indian population [16][17][18][19][20][21]. Furthermore, we have documented that the renal and cell integration markers like creatinine, AST and GGT were lower in females than males as supported by previous studies done elsewhere [22,23].…”
Section: Discussionsupporting
confidence: 84%
“…Recent studies from different geographical locations of India have established reference intervals for certain biochemical parameters and also identified significant changes in liver markers and lipid levels in healthy Indian population [16][17][18][19][20][21]. Furthermore, we have documented that the renal and cell integration markers like creatinine, AST and GGT were lower in females than males as supported by previous studies done elsewhere [22,23].…”
Section: Discussionsupporting
confidence: 84%
“…According to the latest ATP III guideline the optimal level of TC, TG, HDL and LDL are < 200 mg/dl, < 150 mg/dl, > 40 mg/dl and < 100 mg/dl respectively 26 . Madhumita et al has shown from a study conducted on 1485 Assamese subjects that an average healthy urban Assamese population has a TC, TG, HDL and LDL value of 170 mg/dl, 110 mg/dl, 40 mg/dl and 103 mg/dl respectively 27 . Considering the ATP III criteria as well as the values provided by study of Madhumita et al, the hyperuricemic cases in the present study are associated with dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Available global data have clearly established the relationship of lipids and other risk factors with cardiovascular and cerebrovascular events [3][4][5][6][7][8][9][10][11]. It is therefore essential to establish a reference range of the values of serum lipids for a given population as only a few studies have been carried out in other regions of India [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%